(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate and compare the effectiveness of Unna’s boot and ozone therapy on chronic venous leg ulcers. Seven patients with chronic venous leg ulcers were taken into the study and were randomly divided into two groups: Unna’s boot treatment group (BU); Ozone treatment group (OZ). The therapies were performed weekly until wound closure. The morphological descriptive results demonstrated that during the treatments, it was possible to observe the presence of semi-planar borders, granulation tissue, reduction of edema, fibrin and exudate and absence of odor. These morphological modifications were more pronounced in the OZ when compared to the BU. Furthermore, both treatments promoted the same wound healing time, never the less the ozone therapy produced a higher percentage of weekly wound reduction compared to Unna’s boot. Unna’s boot and ozone therapy treatments appeared to positively impact the course of wound healing in chronic wounds, however the ozone therapy may improve the healing of chronic venous leg ulcers in a higher weekly percentage.